Continuous Hemodynamic Monitoring in an Intact Rat Model of Simulated Diving - Gaustad, Svein E.; Kondratiev, Timofei V.; Eftedal, Ingrid; Tveita, Torkjel (Frontiers in Physiology, 2020)
Cardiovascular risk is elevated in divers, but detailed information of cardiac function during diving is missing. The aim of this study was to apply an intact rat model with continuous monitoring of cardiac left ventricular (LV) function in a simulated diving experiment. Thirteen rats were inserted with a LV pressure-volume catheter and a pressure transducer in the femoral artery to measure hemodynamic variables, and randomly assigned to diving (n=9) and control (n=4) groups. The diving group was compressed to 600 kPa in air, maintained at pressure for 45 min (bottom phase), and decompressed to surface at 50 kPa/min. Data was collected before, during, and up to 60 min after exposure in the diving group, and at similar times in non-diving controls. During the bottom phase, stroke volume (SV) (-29%) and cardiac output (-30%) decreased, whereas LV end-systolic volume (+13%), mean arterial pressure (MAP) (+29%), and total peripheral resistance (TPR) (+72%) increased. There were no changes in LV contractility, stroke work, or diastolic function. All hemodynamic variables returned to baseline values within 60 min after diving. In conclusion, our simulated dive experiment to 600 kPa increased MAP and TPR to levels which caused a substantial reduction in SV and LV volume output. The increase in cardiac afterload demonstrated to take place during a dive is well tolerated by the healthy heart in our model, whereas in a failing heart this abrupt change in afterload may lead to acute cardiac decompensation.